1990
DOI: 10.1557/jmr.1990.2305
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen in diamond deposition by microwave plasma enhanced chemical vapor deposition

Abstract: High quality diamond thin films were deposited on different substrates at temperatures from 300 to 1000 °C by the microwave plasma enhanced chemical vapor deposition (MPCVD) system. The quality of deposited diamond films was improved by adding oxygen in the gas mixtures. Different ratios of methane to oxygen concentration in hydrogen at different temperatures have been studied. At high temperatures (800–1000 °C), the addition of oxygen will not only enhance the growth rate of deposited films but also extend th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…Several studies have reported enhanced growth rates or quality due to oxygen addition and, more importantly, the substrate temperature can be significantly lowered when oxygen is introduced into the hydrocarbon/H 2 gas mixtures [73][74][75][76][77][78].…”
Section: Effect Of Oxygen Additionmentioning
confidence: 99%
“…Several studies have reported enhanced growth rates or quality due to oxygen addition and, more importantly, the substrate temperature can be significantly lowered when oxygen is introduced into the hydrocarbon/H 2 gas mixtures [73][74][75][76][77][78].…”
Section: Effect Of Oxygen Additionmentioning
confidence: 99%
“…We have also produced with the same design of the stage a high-quality 0.6-mm-thick pure-CVD single crystal by adding a small amount of oxygen and lowering the growth temperature to 800-1,000°C at 0.2-2% O 2 ͞CH 4 , 1-7% CH 4 ͞H 2 , and 160 torr. The added oxygen allows a lower growth temperature, which removes the nitrogen-related impurities and reduces the silicon and hydrogen impurity levels (26,27). Although this gives a lower growth rate of Ϸ10 m͞h, the rate is still over 1 order of magnitude higher than that of standard processes, typically 0.3 m͞h (26,27).…”
mentioning
confidence: 99%
“…The added oxygen allows a lower growth temperature, which removes the nitrogen-related impurities and reduces the silicon and hydrogen impurity levels (26,27). Although this gives a lower growth rate of Ϸ10 m͞h, the rate is still over 1 order of magnitude higher than that of standard processes, typically 0.3 m͞h (26,27). This high-quality diamond may be very useful in high-power laser window applications.…”
mentioning
confidence: 99%
“…One explanation for such a coloration is the association with nitrogen-vacancyhydrogen (NVH -) complex centers [27]. On the other hand, addition of oxygen to the CVD diamond-growth chemistry can also facilitate the diamond formation [28]. New species formed in the plasma (i.e., O -and OH -) etch away impurities (hydrogen, and sp 2 carbon) and defects on growth surface more efficiently than atomic hydrogen, and therefore improve the diamond quality.…”
Section: Optical Characterization Of Cvd Single-crystal Diamondmentioning
confidence: 99%